PENGEMBANGAN MEDIA PEMBELAJARAN BOARD GAME “PROBABILITY QUEST” PADA MATERI PELUANG UNTUK SISWA KELAS X DI SMA TERPADU WIRA BHAKTI GORONTALO - Nurdian Siama; Syamsu Qamar Badu; Khardiyawan A.Y. Pauweni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by students' difficulties in understanding mathematical concepts, specifically the probability topic, which is often considered abstract and tedious, combined with the school's policy of limiting digital device usage during class hours. As a solution, this study aims to describe the development process of a non-digital learning tool in the form of the